PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Sekarningsih, Ayu (tesco publisher, 2023)
The research aims to determine the effect of liquidity and leverage on accounting conservatism with financial distress as an intervening variable in property and real estate companies for the 2021 period. This type of research is causal associative. The sampling method used was purposive sampling. The total population of property and real estate companies is 85 companies and a sample of 55 companies is obtained. The research method used is path analysis. Based on the results of data analysis, partially 1) liquidity has no effect on financial distress, 2) leverage has an effect on financial distress, 3) liquidity has no effect on accounting conservatism, 4) leverage has an effect on accounting conservatism, 5) financial distress has no effect on accounting conservatism, 6) financial distress cannot intervene the effect of liquidity on accounting conservatism, 7) financial distress cannot intervene the effect of leverage on accounting conservatism.